ANALISIS PROTEIN ISOLAT BAKTERI Escherichia coli BL 21 MENGGUNAKAN Sodium Dodecyl Sulphate – Polyacrylamide Gel Elektrophoresis (SDS-PAGE) - Eka Oktaviani; Maya Ekaningtias (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2019)
Protein is a structural and functional component found in living organisms. This study aims to determine the quantity of protein obtained and the type of protein that was successfully extracted from the culture of Escherichia coli BL 21 (DE3). The research method uses exploratory descriptive, measurement of protein concentration by spectrophotometer and analysis of protein molecular weight by SDS-PAGE electrophoresis. The results of the study it was found that the total protein isolated from E. coli BL21 (DE3) bacterial culture had a concentration of 7.67 µg / µl, the control concentration was higher than the sample which was 9.33 µg / µl. The conclutions of the study it was found that the concentration of total protein isolated from E. coli BL21 (DE3) bacterial culture had a of 7.67 µg/µl, but the molecular weight and type of protein in total protein were still unknown.